Use of Twitter Amplifiers by Medical Professionals to Combat Misinformation During the COVID-19 Pandemic - Regina Royan; Tricia Rae Pendergrast; Marina Del Rios; Shannon M Rotolo; N Seth Trueger; Eve Bloomgarden; Deanna Behrens; Shikha Jain; Vineet M Arora (JMIR Publications, 2022)
Social media is an important tool for disseminating accurate medical information and combating misinformation (ie, the spreading of false or inaccurate information) and disinformation (ie, spreading misinformation with the intent to deceive). The prolific rise of inaccurate information during a global pandemic is a pressing public health concern. In response to this phenomenon, health professional amplifiers such as IMPACT (Illinois Medical Professional Action Collaborative Team) have been created as a coordinated response to enhance public communication and advocacy around the COVID-19 pandemic.